Health Information Exchange: Understanding the Policy Landscape and Future of Data Interoperability - Holmgren, A Jay; Esdar, Moritz; Hüsers, Jens; Coutinho-Almeida, João (Yearbook of Medical Informatics, 2023)
Objectives: To review recent literature on health information exchange (HIE), focusing on the policy approach of five case study nations: the United States of America, the United Kingdom, Germany, Israel, and Portugal, as well as synthesize lessons learned across countries and provide recommendations for future research.Methods: A narrative review of each nation’s HIE policy frameworks, current state, and future HIE strategy.Results: Key themes that emerged include the importance of both central decision-making as well as local innovation, the multiple and complex challenges of broad HIE adoption, and the varying role of HIE across different national health system structures.Conclusion: HIE is an increasingly important capability and policy priority as electronic health record (EHR) adoption becomes more common and care delivery is increasingly digitized. While all five case study nations have adopted some level of HIE, there are significant differences across their level of data sharing infrastructure and maturity, and each nation took a different policy approach. While identifying generalizable strategies across disparate international systems is challenging, there are several common themes across successful HIE policy frameworks, such as the importance of central government prioritization of data sharing. Finally, we make several recommendations for future research to expand the breadth and depth of the literature on HIE and guide future decision-making by policymakers and practitioners.
Keywords: Health Information Exchange; interoperability; data sharing; health information technology; electronic health records